2021
DOI: 10.21037/tau-20-1056
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the risk factors of cardiovascular disease by testing biochemical markers and young men with erectile dysfunction: a case-control study

Abstract: Background: Erectile dysfunction (ED) shares common risk factors with cardiovascular disease (CVD), such as diabetes mellitus (DM) and dyslipidemia, but the relationship between the risk factors of CVD in biochemical markers and young men with ED age 20-40 years is not fully clarified.Methods: A total of 289 ED outpatients (20-40 years old) were allocated under ED group, based on patients' complaints and physical examinations. According to the frequency matching ratio of 1:4, 1,155 male individuals (20-40 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…ED is a significant vascular condition linked closely with risk factors like hyperlipidemia, metabolic syndrome, diabetes, inflammation, hypertension, and vascular endothelial function ( Balta and Mikhailidis, 2019 ). Research by Ma et al indicates that elevated LDL levels can increase the incidence of ED in youthful males ( Ma et al, 2021 ). Currently, nitric oxide (NO) synthesis and release play a crucial role in erectile function, being considered the primary factor in the relaxation of penile blood vessels and the corpus cavernosum ( Andersson, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…ED is a significant vascular condition linked closely with risk factors like hyperlipidemia, metabolic syndrome, diabetes, inflammation, hypertension, and vascular endothelial function ( Balta and Mikhailidis, 2019 ). Research by Ma et al indicates that elevated LDL levels can increase the incidence of ED in youthful males ( Ma et al, 2021 ). Currently, nitric oxide (NO) synthesis and release play a crucial role in erectile function, being considered the primary factor in the relaxation of penile blood vessels and the corpus cavernosum ( Andersson, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mental disorders like depression and cardiovascular diseases like coronary heart disease have been linked with ED [5] , [11] . However, other observational studies do not support the association between coronary heart disease, sleep disorders, cigarette and alcohol consumption, dyslipidemia and ED [12] , [13] , [14] , [15] , [16] , [17] . A Mendelian Randomization (MR) study has also indicated a null association between lipid levels and ED [18] .…”
Section: Introductionmentioning
confidence: 88%
“…By definition, ED is the persistent or recurrent inability of a male to achieve and maintain adequate penile erection sufficient for satisfactory sexual function, as part of the overall multifaceted process of male sexual function [5]. Erectile dysfunction is either primary or secondary in origin.…”
Section: Introductionmentioning
confidence: 99%